Spare Time as one of the Dimensions of the Everyday Life of Children Living in Poland and Portugal - Teresa Parczewska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The objective of this article is to demonstrate the experiences of Polish and Portuguese children at an early-school age connected with the ways of spending their spare time after completing their daily school curriculum. Numerous research projects indicate the shrinking of spare time in families and the tendency to spend less and less time outdoors, in natural surroundings. Many researchers around the world have noticed that electronic media fill up not only the spare time of children, but are also used during classes. The issue at hand sheds light on the contemporary trends associated with the issue of spare time.